2023
DOI: 10.1097/sap.0000000000003457
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Immediate Lymphatic Reconstruction in Prevention of Breast Cancer–Related Lymphedema

Abstract: Introduction Breast cancer–related lymphedema (BCRL) is a chronic condition that can negatively affect the quality of life of breast cancer survivors. Immediate lymphatic reconstruction (ILR) at the time of axillary lymph node dissection is emerging as a technique for the prevention of BCRL. This study compared the incidence of BRCL in patients who received ILR and those who were not amenable to ILR. Methods Patients were identified through a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…To date, of the 411 patients that we have attempted ILR, we were unable to complete ILR in 52 patients (12.7%) due to a lack of visualized lymphatics or anatomic variability (e.g., spatial relationships or size discrepancies). 17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, of the 411 patients that we have attempted ILR, we were unable to complete ILR in 52 patients (12.7%) due to a lack of visualized lymphatics or anatomic variability (e.g., spatial relationships or size discrepancies). 17…”
Section: Discussionmentioning
confidence: 99%
“…To date, of the 411 patients that we have attempted ILR, we were unable to complete ILR in 52 patients (12.7%) due to a lack of visualized lymphatics or anatomic variability (e.g., spatial relationships or size discrepancies). 17 In the clinic, regular monitoring of patients with a dedicated team including a certified plastic surgery nurse (CPSN), a certified lymphatic therapist (CLT), dietician and plastic surgeon helps to detect and manage any subclinical/early-stage disease. This affords the opportunity to optimize the results of secondary surgical interventions to treat BCRL should the need arise.…”
Section: Manuscriptmentioning
confidence: 99%
“…Reported rates of lymphedema following ILR are significantly lower than the cohort without intervention, in the range of 3%-12% compared with a historic 20%-40%. 2,[4][5][6][7][8] Recently published preliminary results of a randomized controlled trial are promising and supportive of the meaningful impact ILR has on reducing the risk of BCRL. 9 Despite our progress in the field with retrospective institutional studies, systematic reviews, meta-analysis, and randomized controlled trials underway, relatively little is known about factors that may contribute to procedural failure or the protective nature this intervention has on high-risk patients despite other high-risk comorbidities.…”
Section: Introductionmentioning
confidence: 88%
“…Literature suggests this may impact up to 40% of high-risk breast cancer survivors. [1][2][3] Breast cancer-related lymphedema is a life-altering diagnosis following cancer treatment and imparts a significant, multidimensional impact on patients. Avariety of therapeutic treatment modalities exist, which include complete decongestive and compression therapy for symptomatic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Some retrospective studies of the effectiveness of ILR have recently been published ( 4 , 5 ). In a recent report with a relatively large number of cases, Le et al reported that in 252 patients treated with ILR, BCRL occurred in 4.8% of patients, compared with 24.1% in 29 patients not treated with ILR, indicating that ILR was effective in preventing BCRL ( 6 ). Hill et al also conducted a systematic review and meta-analysis of the efficacy of ILR for BCRL.…”
mentioning
confidence: 99%